Early changes in 25-hydroxyvitamin D levels and bone markers after monthly risedronate with cholecalciferol in Korean patients with osteoporosis - Chung, Ho Yeon (Dove Medical Press, 2013)
PURPOSE: This study investigated the efficacy and safety of monthly risedronate, with and without cholecalciferol, on 25-hydroxyvitamin D (25[OH]D) levels and bone markers in Korean patients with osteoporosis. METHODS: A randomized, double-blinded, prospective, 16-week clinical trial was conducted in ten hospitals. A total of 150 subjects with osteoporosis were randomized to one of the two treatment groups: RSDM+ (monthly risedronate 150 mg and cholecalciferol 30,000 IU combined in a single pill, n = 74) or RSDM (monthly risedronate 150 mg alone, n = 76). We measured serum levels of 25-hydroxyvitamin D (25[OH]D), parathyroid hormone (PTH), and bone markers, as well as performing muscle-function tests at baseline and after 16 weeks of treatment. RESULTS: After 16 weeks, serum 25(OH)D levels significantly increased from 17.8 to 26.8 ng/mL in the RSDM+ group, but did not change in the RSDM group. The RSDM+ group exhibited significantly decreased serum PTH from 46 to 36.7 pg/mL, while the RSDM group showed a tendency for PTH to increase from 38 to 40.6 pg/mL. In both groups, serum bone-specific alkaline phosphatase and C-terminal telopeptide rapidly declined, with significance at 16 weeks; there were no significant differences between the groups. CONCLUSION: A once-monthly pill of risedronate and cholecalciferol provided equivalent antiresorptive efficacy to risedronate alone in terms of bone turnover and improved 25(OH)D levels over the 16-week treatment period without significant adverse events in Korean patients with osteoporosis.